2018
DOI: 10.1016/j.healthpol.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Financial protection in Europe: a systematic review of the literature and mapping of data availability

Abstract: The literature provides little actionable evidence on financial protection in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…On the measurement issue of social inclusion in health systems and health insurance, a study published by WHO on financial protection in Europe, found that the association between gaps in population coverage and financial hardship is weak because people lacking coverage usually only account for a small share of the population, and European countries generally provide all residents with access to emergency services, which is often not the case in LMIC [123]. However, the incidence of catastrophic health spending and financial protection still varies hugely among households in Europe, especially among countries that joined the EU after 30 April 2004 [123, 124]. Similar strategies, such as exemptions for poor people and regular users of health services – e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the measurement issue of social inclusion in health systems and health insurance, a study published by WHO on financial protection in Europe, found that the association between gaps in population coverage and financial hardship is weak because people lacking coverage usually only account for a small share of the population, and European countries generally provide all residents with access to emergency services, which is often not the case in LMIC [123]. However, the incidence of catastrophic health spending and financial protection still varies hugely among households in Europe, especially among countries that joined the EU after 30 April 2004 [123, 124]. Similar strategies, such as exemptions for poor people and regular users of health services – e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since the seminal work by Xu et al [6], a large body of literature on the incidence of CHE has emerged and developed. However, in a systematic review of literature [7] several gaps were identified, namely the scarcity of up-to-date analysis and a bias of the literature towards middle-income countries. Few studies analysed trends over time and not many developed equity analyses (and most equity analyses correspond to the calculation of CHE by expenditure or income quintiles).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being easy to calculate, the measure is intuitively appealing. Both characteristics have contributed to its widespread application (Limwattananon et al, 2007;Van Doorslaer et al, 2007;Xu et al, 2007;Dmytraczenko and Almeida, 2015;Cylus et al, 2018;Wang et al, 2018;Yerramilli et al, 2018).…”
Section: Catastrophic Paymentsmentioning
confidence: 99%